Development of System Identification for Piezoelectric Patch Actuator - Maslan, Mohd Nazmin; Jamaludin, Zamberi; A Rahman, Muhamad Arfauz; Abdullah, Lokman; Abd Latib, Mohd Lutfan; Karjanto, Juffrizal; Mailah, Musa (Trans Tech Publications Inc., 2014)
This paper presents the development of the system identification (SI) for the highly nonlinear piezoelectric patch actuator. The transfer function is determined by using the nonlinear least square (NLS) method after the direct measurements of input-output data are taken from the actuator that is installed on a well-equipped platform. The results were validated to ensure that the transfer function derived fits well with the experimental output.